Twilight of the elves - Clark, Zack Loran; Eliopulos, Nick (Clark, Zach Loran. Adventurers guild, 2019)
After fleeing their city, the elves have taken refuge in Freestone. But tensions rise as resources are strained with more inhabitants in the community. And when a small group returns to the abandoned city hoping to save it, they are faced with a powerful magic that forces them to work together and fight harder than ever before.